2022
DOI: 10.1128/spectrum.02160-22
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing-Based Species Classification, Multilocus Sequence Typing, and Antimicrobial Resistance Mechanism Analysis of the Enterobacter cloacae Complex in Southern China

Abstract: The presence and emergence of multiple species/subspecies of ECC have led to diversity and complications at the taxonomic level, which impedes our further understanding of the epidemiology and clinical significance of species/subspecies of ECC. Accurate identification of ECC species is extremely important.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…Among these genes, beta-lactamase ACT ( blaACT ), fosfomycin resistance glutathione transferase ( fosA ), and multidrug efflux RND transporters ( oqxA and oqxB ) were consistently found in all strains belonging to the novel Enterobacter species. It is worth mentioning that blaACT genes were the most dominant beta-lactamase genes found among the members of the E. cloacae complex ( 2 ). Additionally, homologs of fosA , which contribute to intrinsic fosfomycin resistance ( 51 ), were present in the majority of genomes of several Enterobacteriaceae species including E. cloacae .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these genes, beta-lactamase ACT ( blaACT ), fosfomycin resistance glutathione transferase ( fosA ), and multidrug efflux RND transporters ( oqxA and oqxB ) were consistently found in all strains belonging to the novel Enterobacter species. It is worth mentioning that blaACT genes were the most dominant beta-lactamase genes found among the members of the E. cloacae complex ( 2 ). Additionally, homologs of fosA , which contribute to intrinsic fosfomycin resistance ( 51 ), were present in the majority of genomes of several Enterobacteriaceae species including E. cloacae .…”
Section: Resultsmentioning
confidence: 99%
“…The focus of this study is the Enterobacter cloacae complex (ECC), which comprises several difficult-to-discriminate species of Enterobacter ( 1 ). ECC members are known to include nosocomial pathogens responsible for infections such as pneumonia, septicemia, and urinary tract infections ( 2 ). Additionally, Enterobacter is part of the ESKAPE group and also contains several multidrug-resistant pathogens ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…To date, the mcr-9 gene has been associated with the co-occurrence of carbapenemase genes bla VIM , bla IMP , bla KPC , and bla NDM-1 [10] , [24] , [44] , [45] , however, case reports about co-existence of mcr-10 and carbapenemase genes ECC are still rare. A study has reported that the bla ACT gene was most prevalent among the ECC and its variants ( bla ACT-2 , bla ACT-3 ) were only present in E. asburiae [46] . In our findings, the bla ACT-3 genes were identified in all ST252 E. asburiae , indicating that it serves as a reservoir for bla ACT-3 genes.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance in these bacteria is also mediated by high expression of bacterial efflux pumps, decreased expression or loss of membrane pore proteins ompF and ompC, and alteration of drug binding sites. 1 , 11 , 12 Notably, ESBL-producing Enterobacterales were classified as one of the most significant pathogens in the World Health Organization’s list of priority pathogens. 13 , 14 A nationwide survey conducted in China revealed that the prevalence of ESBL-producing Enterobacterales was as high as 40.6%.…”
Section: Introductionmentioning
confidence: 99%